Sectarianism: Nature and Defining Criteria - Fareed Hameed Al-Hindawi; Basim Jubair Kadhim (RIRAI Publisher, 2021)
This paper investigates the linguistic account of sectarianism in terms of definition, forms, defining criteria, types of sectarianism and all the strategies which may represent sectarianism within a certain society. To define the sectarian discourse, defining criteria as well as parameters to specify the discourse genre which is related to sectarianism are to be explored and discussed. This can set the blueprints of analysis of the sectarian discourse.